Serum Liver‐Type Fatty Acid–Binding Protein Is a Possible Prognostic Factor in Human Chronic Liver Diseases From Chronic Hepatitis to Liver Cirrhosis and Hepatocellular Carcinoma. Issue 6 (2nd April 2019) - Eguchi, Akiko; Hasegawa, Hiroshi; Iwasa, Motoh; Tamai, Yasuyuki; Ohata, Keiichi; Oikawa, Tsuyoshi; Sugaya, Takeshi; Takei, Yoshiyuki
Abstract : Liver‐type fatty acid–binding protein (L‐FABP) is a key regulator of fatty acid metabolism, but serum L‐FABP levels are not well investigated in chronic liver diseases. We aimed to elucidate the prognostic ability of serum L‐FABP in human chronic liver diseases and compare it with the albumin‐bilirubin (ALBI) score. In 242 chronic liver disease patients, including chronic hepatitis (CH, n = 100), liver cirrhosis (LC, n = 142), and presence of hepatocellular carcinoma (HCC, n = 144), serum L‐FABP levels were correlated with liver function ( P  < 0.0001), increased in LC compared with CH ( P  < 0.01), and correlated to ALBI score ( P  < 0.0001). Serum L‐FABP levels were increased in the presence of HCC ( P  < 0.0001), correlating to des‐gamma‐carboxy prothrombin ( P  < 0.0001), alpha‐fetoprotein ( P  = 0.009), and Barcelona‐Clinic Liver Cancer stage. In the average follow‐up period of 1, 054 days, serum L‐FABP levels were elevated ( P  < 0.0001) in patients who eventually died. The area under the curve (AUC) of serum L‐FABP (0.764) was higher than that of ALB (0.709), and the patients with serum L‐FABP ≤ 6.8 ng/mL had significantly longer rates of survival ( P  < 0.0001). Serum L‐FABP (hazard ratio [HR] 4.0; P  < 0.001), HCC (HR 3.7; P  = 0.001), ALBI score (HR 2.7; P  < 0.001), and age (HR 1.0; P  = 0.049) were independent predictors of survival. In the subgroup who maintained liver function, the AUC of serum L‐FABP (0.751) was higher than that of ALB (0.643). In this subgroup, serum L‐FABP (HR 4.4; P  = 0.002) and HCC (HR 13.9; P  < 0.001) were independent predictors of survival. Conclusion: Serum L‐FABP is a possible predictor of survival in chronic liver diseases from CH to LC and HCC, including any subgroup that maintains liver function. Abstract : Serum L‐FABP levels were significantly increased in the deceased group. Receiver operating curve analyses yielded area under the curve values of 0.765 (95% CI: 0.6989 to 0.8303) for serum L‐FABP levels, which was better than an AUC value of 0.709 (95% CI: 0.6363 to 0.7812) for Alb levels. The cutoff value of serum L‐FABP levels was 6.8 ng/mL.